Endometrial glucose metabolism during early pregnancy - Ziting Chen; Matthew Dean (Bioscientifica, 2023)
Approximately 50% of pregnancies in humans fail, mostly before or during implantation. One factor contributing to pregnancy loss is abnormal glucose metabolism in the endometrium. Glucose contributes to preimplantation embryo development, uterine receptivity, and attachment of the embryo. Across multiple species, the epithelium stores glucose as the macromolecule glycogen at estrus. This reserve is mobilized during the preimplantation period. Glucose from circulation or glycogenolysis can be secreted into the uterine lumen for use by the embryo or metabolized via glycolysis, producing ATP for the cell. The resulting pyruvate could be converted to lactate, another important nutrient for the embryo. Fructose is an important nutrient for early embryos, and the epithelium and placenta can convert glucose to fructose via the polyol pathway. The epithelium also uses glucose to glycosylate proteins, which regulates embryo attachment. In some species, decidualization of the stroma is critical to successful implantation. Formation of the decidua requires increased glucose metabolism via the pentose phosphate pathway and glycolysis. After decidualization, the cells switch to aerobic glycolysis to produce ATP. Paradoxically, the decidua also stores large amounts of glucose as glycogen. Too little glucose or an inability to take up glucose impairs embryo development and decidualization. Conversely, too much glucose inhibits these same processes. This likely contributes to the reduced pregnancy rates associated with conditions like obesity and diabetes. Collectively, a precise control of glucose metabolism is important for several endometrial processes required to establish a successful pregnancy. The factors regulating these metabolic processes remain poorly understood.